Carotid cavernous fistula with retrograde flow to cortical veins successfully treated with endovascular detachable balloon - Ramadhoni, Pinto Desti; Nuraini, Minda (International Journal of Research in Medical Sciences, 2022)
A carotid-cavernous fistula (CCF) is an abnormal vascular connection, which allows blood to flow either directly or indirectly from the carotid artery into the cavernous sinus. The classic triad of ocular symptoms mostly seen in direct CCFs but less common without ocular symptoms. This difference in symptoms depends on the draining venous flow from the fistula, whether it affects the ophthalmic veins or affects the cortical veins. We presented a case of a 32-year-old man with decreased consciousness, seizures, vomiting, a history of long-standing headache, ringing in the ears and double vision, without ptosis, opthamoplegia and without proptosis. Head CT showed a sulcal and perimesencepalic type of subarachnoid hemorrhage. Digital subtraction angiography (DSA) results obtained arterial vein fistula from the right internal carotid artery to the cavernous sinus with the dominant vein draining into the cortical vein, accompanied by dilatation and elongation of the cortical veins. No disturbances in ophthalmic venous outflow were found. Endovascular therapy was performed to close the fistula with detachable balloon embolization modality, with the result of complete fistula closure. The symptom pattern of CCF depended on flow velocity, location of CCF venous drainage, inflammation and pressure within the venous sinuses. Cerebral catheter angiography is the gold standard imaging modality used in the diagnosis and classification of CCF and embolization using a detachable balloon is one of the treatment options for direct CCF.